ORAL CORRECTIVE FEEDBACK IN SPEAKING CLASS: ITS FREQUENCY, STUDENTS’ PERCEPTIONS AND PREFERENCE - Anita Fatimatul Laeli; Slamet Setiawan (Universitas Muhammadiyah Makassar, 2019)
The objective of this qualitative study is to investigate kinds of corrective feedback used by the English lecturer in speaking class at English Department in one of private University in Jember. Further, this research also investigate how the students’ perception and preference lying on their speaking proficiency toward the corrective feedback which is dominantly used by the lecturer. Based on the analysis taken from questionnaire given to 30 students of English Language Education department, it was found that (1) recast, repetition and clarification request are commonly used in the class. And (2) according to the students’ perceptions, repetition is the effective feedback that engage the students to improve their speaking skill. Last (3) the students prefer to get repetition and explicit correction as the feedback in the speaking class.